Correction: Study of thermal material properties for Ta- and Al-substituted Li7La3Zr2O12 (LLZO) solid-state electrolyte in dependency of temperature and grain size. Issue 39 (20th September 2022) - Neises, Julian; Scheld, Walter Sebastian; Seok, Ah-Ram; Lobe, Sandra; Finsterbusch, Martin; Uhlenbruck, Sven; Schmechel, Roland; Benson, Niels
Abstract : Correction for 'Study of thermal material properties for Ta- and Al-substituted Li7 La3 Zr2 O12 (LLZO) solid-state electrolyte in dependency of temperature and grain size' by Julian Neises et al., J. Mater. Chem. A, 2022, 10, 12177–12186, ; https://doi.org/10.1039/D2TA00323F .